Influence of sodium desoxyribonucleate on anti-infectious protection and hematopoiesis in patients with polytrauma (randomized prospective, double-blind, placebo-controlled study) - L. P. Pivovarova; M. I. Gromov; A. N. Tulupov; V. N. Lapshin; I. V. Osipova; O. B. Ariskina; A. V. Nikitin; M. E. Malyshev; E. V. Markelova (Медицинская иммунология)
The  aim of the study was to evaluate  the effect of sodium  deoxyribonucleate on anti-infectious resistance and hematopoiesis in patients with polytraumas. A single-center study of sodium  deoxyribonucleate effectiveness approved by the local Ethics Committee (protocol No. 4 05/18/2016), was conducted in 54 patients with polytrauma. The  main  group  included 27 people, at the mean  age of 39 (29-51)  years old; ISS severity score,  26 (22-34). The  comparison group  comprised 27 people, mean  age,  40 years old (26-53), mean  ISS severity score was 25 points (20 to 29). The patients with randomly attributed even numbers were injected with 5 ml preparation from vials of even-numbered series, the patients with odd numbers were treated with preparation from the odd-numbered series. They were injected intramuscularly daily from day 1 to day 10 after the injury. Before treatment, as well as on days 8, 15 after injury, peripheral blood was examined for leukocyte, erythrocyte counts, hemoglobin, total  protein, blood  IL-6, CRP; proportion of CD117+  and  CD34+  mononuclear cells, CD14+ monocytes, CD14+ granulocytes, HLA-DR+  mononuclear cells, defensin + granulocytes.On  the  day  +8,   patients from  the  main  group,  against  the  comparison group  showed  an  increase   in lymphocytes, monocytes, CD117+ and CD34+ cell counts. Serum IL-6 and CRP were decreased in both groups of the patients to a similar  degree. Terms  of hospitalization in the main  group were 32.8 days, against  39.6 in comparison group. The number of complications per 1 case was, respectively, 21 versus 39, thus being 1.8 times less than  in comparison group.  When developing complications, anemia (Hb  < 90 g/l),  or hypoproteinaemia (< 60 g/l) in the main group was, respectively, 2.5and 3.5-fold  less than  in the comparison group.Treatment with sodium  deoxyribonucleate in polytrauma may promote migration of blood precursors to the bloodstream, increase anti-infectious properties of leukocytes, reduce duration of anemia and hypoproteinemia, number of complications and decrease the terms of hospitalization.